2014
DOI: 10.1136/thoraxjnl-2012-203062
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity but not NLRP3 inflammasome activation correlates with severity of stable COPD

Abstract: BackgroundIn models of COPD, environmental stressors induce innate immune responses, inflammasome activation and inflammation. However, the interaction between these responses and their role in driving pulmonary inflammation in stable COPD is unknown.ObjectivesTo investigate the activation of innate immunity and inflammasome pathways in the bronchial mucosa and bronchoalveolar lavage (BAL) of patients with stable COPD of different severity and control healthy smokers and non-smokers.MethodsInnate immune mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(132 citation statements)
references
References 43 publications
6
122
2
2
Order By: Relevance
“…These data, obtained from stable COPD patients by immunohistochemistry, confirm previously reported higher numbers of neutrophils and CD8+ cells in severe/very severe COPD (Table 4) [28].…”
Section: Measurement Of Inflammatory Cells In the Bronchial Submucosasupporting
confidence: 80%
“…These data, obtained from stable COPD patients by immunohistochemistry, confirm previously reported higher numbers of neutrophils and CD8+ cells in severe/very severe COPD (Table 4) [28].…”
Section: Measurement Of Inflammatory Cells In the Bronchial Submucosasupporting
confidence: 80%
“…This study reported lack of NLRP3 inflammasome activation in COPD, with no differences in caspase-1 activation, IL-1b, or IL-18 levels in bronchial biopsies or in BAL between the groups (46). It remains conceivable of a role of the inflammasome system in toxic reactions to CS exposure, as well as a component of immune reactions during secondary infections associated with COPD.…”
Section: Inflammasomes In Airways Diseasesmentioning
confidence: 86%
“…Moreover, NLRP3 inflammasome activation has been linked to neutrophilic asthma [19], while inflammasome-regulated cytokines are critical mediators of acute lung injury [20]. Alternatively, a recent report suggests that the NLRP3 inflammasome pathway is not linked to the severity of stable chronic obstructive pulmonary disease following analyses in the bronchoalveolar lavage fluid (BALF) and cellular components [21]. Recent evidence showing a possible activation of NLRP3 by cigarette smoking, another environmental risk factor for both IPF and rheumatoid arthritis, further supports the possible implication of inflammasomes in lung fibrosis [10,18].…”
Section: Introductionmentioning
confidence: 99%